Analysis of the Utilization of Artificial Intelligence Technology in Learning in Indonesia Learning Alignment - Handi Pradana; Fazhar Restu Fauzi; Diena Rauda Ramdania (Southeast Asian Journal on Open and Distance Learning, 2023)
In the contemporary digital era, integrating Artificial Intelligence (AI) into educational practices is vital for enhancing educational effectiveness. This study assesses the readiness of educational institutions in Indonesia, and to some extent in regions like Taipei, Thailand, Malaysia, and Lao PDR, to adopt AI in their learning processes. Employing an Exploratory Research approach, the study involved a Likert scale-based survey with 250 respondents, including educators and students from various educational levels, predominantly from Vocational and Secondary High Schools, as well as Higher Education Institutions. Findings indicate a moderate level of preparedness among educators and students for AI integration in education. Educators exhibit basic digital skills but show significant variation in AI-related competencies, highlighting the need for enhanced professional development in AI learning strategies. Students display moderate access to AI-supportive technology and a foundational understanding of AI applications and digital ethics, suggesting a necessity for improved digital literacy training and resources. The study underscores the importance of structured AI-specific training and collaboration among educational stakeholders to optimize AI's potential in education.